The Baltic states’ foreign policy goals and strategies regarding Russia in 1990s - Valodzkin, Andrei A. (Journal of the Belarusian State University. International Relations, 2019)
Unlike many other publications on the topic of the relations between the Baltic states and Russia, where authors focus mostly on Russian interests and goals in the region, this article presents the analysis from the perspective of Lithuanian, Latvian and Estonian interests and goals. The author reveals the main aims that defined policies of the Baltic states towards Russia in 1990s, demonstrates the dynamics of the issues, which constituted the agenda of Baltic-Russian relations in the appropriate period, analyses the strategies used by the Baltic states to implement their goals and interests regarding Russia and assesses their efficiency.
Keywords: foreign policy; Baltic states; Latvia; Lithuania; Estonia; Russia